The Nature of Nurture: Disentangling Passive Genotype–Environment Correlation From Family Relationship Influences on Children's Externalizing Problems - Harold, Gordon T. (American Psychological Association, 2013)
The relationship between interparental conflict, hostile parenting, and children's externalizing problems is well established. Few studies, however, have examined the pattern of association underlying this constellation of family and child level variables while controlling for the possible confounding presence of passive genotype–environment correlation. Using the attributes of 2 genetically sensitive research designs, the present study examined associations among interparental conflict, parent-to-child hostility, and children's externalizing problems among genetically related and genetically unrelated mother–child and father–child groupings. Analyses were conducted separately by parent gender, thereby allowing examination of the relative role of the mother–child and father–child relationships on children's behavioral outcomes. Path analyses revealed that for both genetically related and genetically unrelated parents and children, indirect associations were apparent from interparental conflict to child externalizing problems through mother-to-child and father-to-child hostility. Associations between interparental conflict and parent-to-child hostility across genetically related and genetically unrelated parent–child groupings were significantly stronger for fathers compared to mothers. Results are discussed with respect to the role of passive genotype–environment correlation as a possible confounding influence in interpreting research findings from previous studies conducted in this area. Implications for intervention programs focusing on family process influences on child externalizing problems are also considered.